AN ANALYSIS OF TRANSLATION OF IDIOMS USED IN CONAN DOYLE’S NOVEL “A STUDY IN SCARLET” - Farida Agoes (Jurnal Bahasa Inggris Terapan, 2016)
The article is about an analysis of translation of idioms in the novel by Conan Doyle entitled A Study in Scarlet. Translating idioms is often problematic for a translator because idioms are specific to a single language and rarely have the equivalent in other languages. Therefore, this study was conducted to find out the types of idioms used in the English version of the novel, to find out the strategies used by the translator of the Indonesian version of the novel in translating the English idioms, and to find out the accuracy, acceptability and readability of the translation of the idioms in the novel. In analysing the idioms and their translation, qualitative method was used, and the theories by Fernando (1996), Baker (2011) and Nababan, Nuraini, and Sumardiono (2012) were also used. The finding of the analysis shows that from 60 idioms found, semi-idiom is the type of idioms which is frequently found in the novel (31 idioms or 52%). Besides, it is revealed that translating the idioms by paraphrasing is the strategy which is mostly used by the translator in translating the idioms (38 idioms or 63%). In addition, it is revealed that the translation of idioms in the novel is accurate and acceptable although it is less readable. So, the quality of translation of idioms in the novel is good although it can be still improved.Keywords: accuracy, acceptability and readability of translation, idiom, translation, translation strategies